PRESSURE-TRANSIENT BEHAVIOR WITH WELLBORE STORAGE AND SKIN EFFECTS IN MULTI-POROSITY SYSTEM - Maulana, Fahrizal
Naturally fractured reservoir is a complex system, much more complex than homogenous reservoir. Two or more porosity systems commonly exist and interact in the reservoir. In some ways, traditional dual-porosity is unable to handle this complexity accurately. Moreover, the presence of wellbore storage and skin makes modeling naturally fractured reservoir more challenging. Numerical method becomes an alternative solution in modeling such complex reservoir. But, the problem arises of how to model wellbore storage and skin in commercial reservoir simulator. Therefore, a technique is needed to accommodate those two parameters in multi-porosity system. This study discusses an application of a technique to model a multi-porosity system in a commercial reservoir simulator by considering wellbore storage and skin effects for strata or slab model. Syntetic data is used in order to obtain better and more accurate analysis than using field data. The system is approached by a radial strata model. Each layer is assigned with different properties. One additional grid near well with modified porosity and permeability is created to simulate the behavior of wellbore itself. The system works under transient flow condition. Dual and triple porosity systems are also included as comparisons. The effects of wellbore storage Cd and skin S on pressure behavior of naturally fractured reservoir are observed and analyzed. This technique is simple to apply and might save the license cost of well simulator add-in. Numerical error might occur in early time of production in log-log plot; however, it succesfully depicts the physical meaning of changing skin and wellbore storage in semi-log plot of multi-porosity system.